Multifunctional Nanohybrid of Alumina and Indium Oxide Prepared Using the Atomic Layer Deposition Technique - Duy, Le Thai; Kang, Hyunwoo; Shin, Hee Cheol; Han, Seunggik; Singh, Ranveer; Seo, Hyungtak (ACS Applied Materials and Interfaces, 2021)
Developing new transparent conducting materials, especially those having flexibility, is of great interest for electronic applications. Here, our study on using the ozone-assisted atomic layer deposition (ALD) technique at a low temperature of 200 °C for making an ultrathin, transparent, flexible, and highly electroconducting nanohybrid of indium and aluminum oxides is introduced. Through various characterizations, measurements, and density functional theory-based calculations, excellent electrical conductivity (∼950 S cm-1), transparency (95% in the visible region), and flexibility (bendable angle of 130° for 10 000 cycles) of our nanohybrid oxide thin film with a total layer thickness below 15 nm (2-4 nm for alumina and 10 nm for indium oxide) have been revealed and discussed. Besides, potential sensing applications of our oxide films on a flexible substrate have been demonstrated, such as strain sensors, temperature sensors (25-100 °C, resolution of 0.1 °C), and NO2 gas sensors (0.35-3.5 ppm, optimum operation at 65-75 °C). With the great potential in not only transparent conducting oxide but also sensing applications, our multifunctional nanohybrid prepared using a simple ozone-assisted ALD route opens more room for the applicability of transparent and flexible electronics.
Keywords: Atomic-layer deposition; Deposition technique; Electronics applications; Indium oxide; Lows-temperatures; Nanohybrids; Sensing applications; TCO; Transparent conducting materials; Ultra-thin; aluminum oxide; atomic layer deposition; indium oxide; sensing; TCO